(untitled) (Raparin Journal of Humanities (RJH), 2023)
As is obvious there are many famous poets in Kurdish literature their reputation crossed the borders to be familiar for the other nations, others for any reason couldn`t reach that level That is why focusing on the second group and paying attention to the products they have provided is acknowledged as scientific responsibility, because their product is a valuable Kurdish literature wealth and it`s very important to be preserved. from this point of view, we conducted this research entitled (A.B Hawri`s poetic experience in Kurdish literature),which is the contents of our master`s letter, we`ve highlighted the poet`s live, experience and products, as well as his interpretation and analysis of poetry because he believed that the content of poetry is more important than its form which is the same view that modern poets have about poetry ,he was one of the poets who followed the same innovation in poetry, also we studied his era political and social environment and we knew his perspective about that era`s events through poetry.The we highlighted the literature, intellectual period and his education stage which Hawri went through ,then himself as a teacher was in pursuit of upbringing and educating sons of this country.